Evaluating sarcopenia prevalence and SARC-F effectiveness in elderly Spanish women with RA: a comparative study of EWGSOP criteria - Valencia-Muntalà, Lidia; Gómez-Vaquero, Carmen; Mora, Maribel; Berbel-Arcobé, Laura; Benavent, Diego; Narváez, Javier; Juanola, Xavier; Nolla, Joan M. (Frontiers in Medicine, 2024)
Introduction: The European Working Group on Sarcopenia in Older People (EWGSOP) has put forward two key proposals for diagnosing sarcopenia: the EWGSOP1 in 2010 and the EWGSOP2 in 2019. These proposals are currently the most widely used guidelines for diagnosing sarcopenia. However, data on the prevalence of sarcopenia in patients with rheumatoid arthritis (RA) based on EWGSOP criteria are limited. This study aimed to: a) establish the prevalence of sarcopenia in an elderly Spanish cohort of women with RA using both EWGSOP1 and EWGSOP2 criteria; and b) evaluate the effectiveness of the SARC-F questionnaire in detecting sarcopenia. Methods: In this observational, cross-sectional study, 67 women aged over 65 years who met the ACR 2010 criteria for RA were consecutively recruited from a tertiary university hospital. Assessments included: a) demographic and anthropometric data; b) RA-related variables (disease history, analytical evaluation, activity, disability, quality of life); and c) sarcopenia-related variables (muscle strength, gait speed, skeletal muscle mass, SARC-F questionnaire). The prevalence of sarcopenia was determined using both EWGSOP1 and EWGSOP2 criteria. Furthermore, the effectiveness of the SARC-F questionnaire for detecting sarcopenia were calculated. Results: The prevalence of sarcopenia was 43% according to the EWGSOP1 criteria and 16% according to the EWGSOP2 criteria. Patients diagnosed with sarcopenia based on the latter criteria also met the EWGSOP1's criteria for sarcopenia. Agreement between the two sets of EWGSOP criteria was poor. The SARC-F questionnaire demonstrated an inherently high sensitivity (100%) as well as good specificity (75%) and diagnostic accuracy (79%) in detecting sarcopenia according to EWGSOP2 criteria. Conclusions: The prevalence rate of sarcopenia among elderly Spanish women with RA varies significantly depending on whether EWGSOP1 or EWGSOP2 criteria are applied. The SARC-F questionnaire is effective for predicting sarcopenia when used in conjunction with the EWGSOP2 criteria, which is currently the most accepted standard in clinical practice.